How Were Eye Movements Recorded Before Yarbus?. (August 2015) - Wade, Nicholas J
Alfred Yarbus introduced a new dimension of precision in recording how the eyes moved, either when attempts were made to keep them stationary or when scanning pictures. Movements of the eyes had been remarked upon for millennia, but recording how they move is a more recent preoccupation. Emphasis was initially placed on abnormalities of oculomotor function (like strabismus) before normal features were considered. The interest was in where the eyes moved to rather than determining how they got there. The most venerable technique for examining ocular stability involved comparing the relative motion between an afterimage and a real image. In the late 18th century, Wells compared afterimages generated before body rotation with real images observed following it when dizzy; he described both lateral and torsional nystagmus, thereby demonstrating the directional discontinuities in eye velocities. At around the same time Erasmus Darwin used afterimages as a means of demonstrating ocular instability when attempting to fixate steadily. However, the overriding concern in the 19th century was with eye position rather than eye movements. Thus, the characteristics of nystagmus were recorded before those of saccades and fixations. Eye movements during reading were described by Hering and by Lamare (working in Javal's laboratory) in 1879; both used similar techniques of listening (with tubes placed over the eyelids) to the sounds made during contractions of the extraocular muscles. Photographic records of eye movements during reading were made by Dodge early in the 20th century, and this stimulated research using a wider array of patterns. Eye movements over pictures were examined by Stratton and later by Buswell, who drew attention to the effects of instructions on the pattern of eye movements. In midcentury, attention shifted back to the stability of the eyes during fixation, with the emphasis on involuntary movements. The suction cap methods developed by Yarbus were applied with some success to recording the perceptual effects of retinal image stabilization. It is an historical irony that the accuracy of image stabilization with contact lenses was assessed by comparison with the oldest method for examining eye movements—afterimages.